The Effect of Educandy Game on Social Studies Learning Outcomes of Food Technology Materials in Grade 3 of SD Negeri Cibatok 1 - Filla Lailatul Maghfiroh; Ambar Wati; Nur Ainun Nizah; Iis Yeni Sugiarti; Faisal Rahmat Permana (Pelopor Publikasi Akademika, 2024)
There is minimal use of innovative learning media in schools, especially at the elementary school level, even though in elementary schools students really need help with learning media to understand the material presented by the teacher. Included in class 3 social studies subjects. The aim of this research is to find out student learning outcomes using educational games, so that we can find out students' activities in the learning process in social studies subjects using direct observation methods at school. The subjects of this research were 1 learning media expert and 1 practitioner, namely the teacher. The test subjects were 46 grade 3 students consisting of the experimental class and the control class. Data collection methods are observation, interviews, tests and questionnaires. The data analysis technique used is quantitative descriptive analysis and statistics. The results of the research, namely the results of media validity tests for the Educandy game application, based on assessments from material and media experts supported by teacher and student responses, show that the media validity value is very high and feasible with an average percentage value of 95%. The results of the T-test show that there is a significant difference in student learning outcomes before and after media use. Educandy game learning media in social studies subjects are suitable for use and are effective in improving student learning outcomes.